STUDI EKSPERIMENTAL BETON ADUKAN KERING DENGAN METODE PENGECORAN PIPA BERKATUP PADA AIR LABORATORIUM - Akbar, Ali; ., Herwani; handalan, Cek putra (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2015)
This paper presents the results of an experiment on the casting by pouring into a mold with a confused puddle varies is 25%, 50%, 75%, 100% and 120% of the height of the mold. Specimens made ​​with a cylindrical Æ 15 cm, and 30 cm high. Order to determine the compressive strength and influence on the amount of standing water on the formwork (cylinder). Testing include compressive strength test. In the manufacture of test specimens used methods namely ACI method. Quality concrete is planned fc '= 25 MPa. From the experimental results obtained values ​​Normal Concrete compressive strength characteristics without puddles of 21.14 MPa and the concrete variables in consecutive puddles 6.18 MPa; 2.73 MPa; 2.42 MPa; 2.42 MPa and 1.89 Mpa. When compared with normal concrete without flooding a decline of 74.28%, 82.50%, 90.38%, 85.51% and 86.61%. Key words :compressive strength, concrete normal